Analysis of VGDS and Marshaller Service Education: Comparison of Aircraft Parking Guidance Efficiency - Yeti Komalasari; Ade Avrilla Silaen; Asep M. Soleh; Minulya Eska Nugraha (Utan Kayu Publishing, 2025)
From a transport safety education perspective, aircraft parker guidance ensures aircraft move safely in busy and confined areas. In aviation, technological developments can be seen in driving aircraft parking at airports. The technology is called VDGS, which automatically performs parking guidance. Aircraft parking guidance with VDGS and marshaller services has its advantages and disadvantages. This study aims to measure the efficiency of VDGS and marshaller services in the aircraft parking guidance process. The research method used was descriptive quantitative, collecting data on the distribution of questionnaires to the research respondents, namely AMC personnel and marshallers, totaling 40 people using total sampling. The results of this study show that VDGS is more efficient than marshallers, with an average value of 78.89% higher than marshallers, with a value of 74.7%. The efficiency level of VDGS and marshaller was measured based on seven research indicators: time, precision, satisfaction, coordination, disruption, availability, and poor weather conditions or low visibility. The indicators in this study are a reference for measuring the level of efficiency that can describe the advantages of VDGS and marshallers. The indicators of the success of this study can be seen in the measurable efficiency value of VDGS and Marshaller aircraft parking services as well as efforts to improve the efficiency of marshaller services by increasing personnel competence.